Responses to Perioperative Challenges of Student Nurses in University - Cuervo, Faith; Cabatana, Maria Estela; Villegas, Piluchi Victorina (JPAIR Multidisciplinary Research, 2018)
Nursing is primarily a practical discipline. Thus, clinical learning experience is an integral part in the nursing curriculum. The perioperative setting is challenging, particularly for student nurses with limited exposure to this area. These difficulties cannot be taken for granted because the Operating Room has a profound effect on those who enter it. As personally experienced by the researcher and as observed by nursing curriculum graduates, perioperative exposure entails a different level of stress to student nurses which serve as a challenge and thus the display of varied responses to it. As a clinical instructor always assigned in the Operating Room to supervise student nurses, it is vital to identify the responses to perioperative demands encountered by students. This study aimed to determine the responses of level III student nurses to perioperative challenges. This study utilized the descriptive method using a researcher-made questionnaire with follow-up interviews. The findings revealed that level III student nurses experience physiologic and emotional-behavioral responses to perioperative demands. A weak relationship between the respondents’ profile and their responses was also found out. The researcher recommends implementing the proposed action plan and conducting an investigation to confirm or reject weak relationships between the respondents’ profile and responses to perioperative challenges.